Motivating grassroots governments in low-carbon transition: comparative analysis of two quadripartite evolutionary game - Shui, Li; Chen, Yuchao (Frontiers in Environmental Science, 2025)
Grassroots governments’ low-carbon policies play a pivotal role in shaping the overall performance of the low-carbon transition. Understanding their behavioral logic within China’s multi-level and polycentric governance system is therefore essential for advancing local transitions. This study develops a quadripartite evolutionary game (QEG) model involving municipal governments (MGs), county governments (CGs), township governments (TGs), and enterprises under two governance settings: the pre-pilot routine (PR) and the low-carbon pilot of “municipality-controlled townships” (LPMT). The model examines the determinants of TGs’ low-carbon policy choices under different incentive–constraint configurations. Simulations show that TGs prioritize county-level rewards/punishments and environmental performance metrics in policy decisions under PR, while focus more on municipal-level regulatory probability, intensity, and rewards/punishments under LPMT. The pilot system effectively mitigates the erosion of incentives and constraints under PR. Under identical parameter configurations, the choice of policy in LPMT is more likely to achieve a stable strategic equilibrium between TGs’ choice of incentive policies and enterprises’ active abatement. Conversely, it is easy to fall into the prisoner’s dilemma of punitive policies by TGs and passive emission reduction by enterprises under PR. By capturing the strategic interactions underlying grassroots policy choices within a polycentric governance framework, this study provides novel insights into how incentive–constraint mechanisms can be optimized to strengthen local governments’ motivation for low-carbon transition.